Role of Information Anxiety and Information Load on Processing of Prescription Drug Information Leaflets - Shweta S. Bapat; Harshali K. Patel; Sujit S. Sansgiry (MDPI AG, 2017)
In this study, we evaluate the role of information anxiety and information load on the intention to read information from prescription drug information leaflets (PILs). These PILs were developed based on the principals of information load and consumer information processing. This was an experimental prospective repeated measures study conducted in the United States where 360 (62% response rate) university students (>18 years old) participated. Participants were presented with a scenario followed by exposure to the three drug product information sources used to operationalize information load. The three sources were: (i) current practice; (ii) pre-existing one-page text only; and (iii) interventional one-page prototype PILs designed for the study. Information anxiety was measured as anxiety experienced by the individual when encountering information. The outcome variable of intention to read PILs was defined as the likelihood that the patient will read the information provided in the leaflets. A survey questionnaire was used to capture the data and the objectives were analyzed by performing a repeated measures MANOVA using SAS version 9.3. When compared to current practice and one-page text only leaflets, one-page PILs had significantly lower scores on information anxiety (p < 0.001) and information load (p < 0.001). The intention to read was highest and significantly different (p < 0.001) for PILs as compared to current practice or text only leaflets. Information anxiety and information load significantly impacted intention to read (p < 0.001). Newly developed PILs increased patient's intention to read and can help in improving the counseling services provided by pharmacists.